2014
DOI: 10.1097/dss.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

100 Citation Classics in the Melanoma Literature

Abstract: This study has identified the most significant contributions to melanoma research over the past 63 years and identifies many important scientific breakthroughs and landmarks that have occurred during this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…Several papers have reported analyses of the most‐cited publications in a number of fields of health sciences, including dentistry, where different specialties have also been separately addressed …”
Section: Introductionmentioning
confidence: 99%
“…Several papers have reported analyses of the most‐cited publications in a number of fields of health sciences, including dentistry, where different specialties have also been separately addressed …”
Section: Introductionmentioning
confidence: 99%
“…The bibliometric analyses in other areas also showed that the United States ranked high on the list (13,14). These findings clearly show that the United States is at the forefront of studies on breast cancer.…”
Section: Discussionmentioning
confidence: 50%
“…It has the potential to identify key authors and institutions publishing on individual research topics as well as giving an overview of how health care within a chosen area has evolved over time. [678910]…”
Section: Discussionmentioning
confidence: 99%